Pengaruh Beban Kerja, Disiplin Kerja, dan Work Life Balance terhadap Kinerja Karyawan : Studi Kasus Yayasan Pendidikan Islam Al-Mursyidiyyah Al-Asyirotussyafi’iyyah - Rahman, Ahmad Abdul; Utomo, Rooswhan Budhi (CV. Ulil Albab Corp, 2026)
Employee performance is a crucial factor in determining the success of an organization, including educational institutions. These conditions have the potential to cause stress, fatigue, decreased motivation, and a decline in productivity. This research aims to analyze the effect of workload, work discipline, and work-life balance on employee performance at Yayasan Pendidikan Islam Al-Mursyidiyyah Al-Asyirotussyafi’iyyah. A quantitative method with an associative approach was employed. The population consisted of 75 employees, all of whom were included as the sample using the total sampling technique. Primary data were collected through a Likert scale questionnaire and further examined using validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and the coefficient of determination (R²) with the assistance of SPSS. The results demonstrate that workload, work discipline, and work-life balance significantly affect employee performance, both individually and simultaneously. These findings imply that optimal performance can only be achieved through an integrated approach that combines effective workload management, consistent discipline, and balance between professional and personal life. Consequently, this study underscores the importance of holistic managerial practices in enhancing human resource quality and sustaining productivity in the education sector.